(untitled) (Research, Society and Development, 2023)
Tomato (Solanum lycopersicum) is an important vegetable produced in Brazil, with socioeconomic relevance especially for the State of Amazonas, where it represents a source of income for family farmers. The production of seedlings is an important step, but limited by the cost and quality of the substrates, and the use of agro-industrial residues can be a solution. Different mixtures of substrates with different watering shifts were evaluated to obtain better sources and combinations of substrates, including açaí seeds and/or açaí kernels, chicken manure and soil, with 1-day or 2-day watering shifts. The experimental design was completely randomized, with six treatments with four replications and four plants in each replication, totaling 32 pots. The parameters of dry and fresh matter production of the aerial part and root system, as well as the length of the aerial part and the roots of the plant were evaluated. The effect of the treatments was statistically evaluated by the Tukey test at 5% probability, and the water storage in the soil was evaluated by the Sequential Climatological Water Balance. The research concluded that adequate irrigation management is necessary in the months of August and September for the tomato crop. Plants with one watering shift had better results than those with two days. The treatment açaí seeds + chicken manure 1:1 with a 1-day watering shift was the most effective.